Relationship Of Anxiety With Cooping Mechanisms In Pre Endoskopi Patients Hospital - Pratama, Setto Yudha; Sunirah, Sunirah; Wada, Fauziah H; Nurwahidah, Andi Tenri; Rahmawati, Syifa (Nursing Genius Journal, 2024)
Endoscopic examination is used to diagnose abnormalities of internal organs including the digestive tract, oral cavity, and abdominal cavity, which can make patients feel anxious. Anxiety arises when there is a threat of loss of control, feelings of loss of function, failure of knowledge, and feelings of isolation. Purpose of this study was to determine the relationship between anxiety and coping mechanisms of pre endoscopy patients at BMC Mayapada Hospital. Method used cross sectional. The population in this study were endoscopy patients at BMC Mayapada Hospital from May to July 2023, totaling 50 patients. Sampling using accidental sampling technique and obtained a sample size of 50 respondents. Data analysis techniques using univariate analysis and bivariate analysis. Result Respondents were dominated by patients with the late adult age category (36-45 years), as many as 21 patients, then female gender, as many as 28 patients, an undergraduate educational background of 24 patients, and as many as 35 patients worked as employees. In the coping mechanism variable, 31 people (62%) solved problems with problem focused coping strategies and 19 people (23%) with emotional focused coping strategies. In the anxiety variable, 26 respondents (52%) experienced mild stress, 13 people (26%) moderate stress, and 11 people (22%) severe stress. The p-value of 0.013 <0.05, the correlation coefficient of 0.839 is positive or unidirectional and lies in the interval 0.75 - 0.99 (very strong). Conclusion that there is a significant and very strong relationship between anxiety and coping mechanisms of pre endoscopy patients at BMC Mayapada Hospital. Researchers recommend that nurses provide psychological assistance to patients and families regarding coping strategies.